La modernisation orientale et l’expérience chinoise - Li Peilin (Socio, 2015)
In the past logic of modernization theory, modernization has always been associated with Western society. Based on the ”China experience”, the deep change and transformation of contemporary China, this paper proposes the topic of “Oriental modernization” for the establishment of the post-Western sociology. The discussion of “Oriental modernization” will contribute to the development of modernization theory under the background of the globalization.